2016
DOI: 10.1080/01480545.2016.1236128
|View full text |Cite
|
Sign up to set email alerts
|

Genotoxicity of antiobesity drug orlistat and effect of caffeine intervention: an in vitro study

Abstract: Orlistat can induce DNA damage in human lymphocytes in vitro and caffeine was found to reduce orlistat-induced genotoxicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…Assisting with weight loss, it also lowers blood glucose levels . However, long-term use of orlistat can induce side effects, including diarrhea, increased stool frequency, oily stool, gastrointestinal flatulence, as well as other side effects, , and may also lead to acute pancreatitis . Therefore, the development of efficient, safe, and nontoxic new compounds for weight loss is important.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Assisting with weight loss, it also lowers blood glucose levels . However, long-term use of orlistat can induce side effects, including diarrhea, increased stool frequency, oily stool, gastrointestinal flatulence, as well as other side effects, , and may also lead to acute pancreatitis . Therefore, the development of efficient, safe, and nontoxic new compounds for weight loss is important.…”
Section: Introductionmentioning
confidence: 99%
“…10 However, long-term use of orlistat can induce side effects, including diarrhea, increased stool frequency, oily stool, gastrointestinal flatulence, as well as other side effects, 11,12 and may also lead to acute pancreatitis. 13 Therefore, the development of efficient, safe, and nontoxic new compounds for weight loss is important. Natural compounds derived from plants are characterized by high bioactivity, low toxicity, and extensive resources.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The IC 50 was reached at 30 to 50 times the THL combination MIC. THL genotoxicity was previously documented on lymphocytes from human peripheral blood at 250 μg/ml (Chakrabarti et al, 2017). To our knowledge, our work is the first study on the THL effect on airway epithelium Calu‐3 and A549 cell lines and THP‐1 monocyte cell line.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, some studies have reported that Orlistat, an antiobesty drug, induced DNA damage in human cells, which suggested that regular consumption of orlistat needs careful circumspection [ 32 ]. In contrast, flavonoids from cocoa in dark chocolate are able to significantly decrease important risk factors such as waist circumference, total cholesterol, LDL-cholesterol, and triglycerides, without causing DNA damage, even having a celluloprotective effect that could reverses the DNA damage in buccal epithelial cells, which is apparently caused by the systemic inflammation of obesity, along with the fact that flavonoids have been long recognized for their anti-inflammatory effect [ 33 ].…”
Section: Discussionmentioning
confidence: 99%